“Recueil d’Architecture Civile” of J.-Ch. Krafft and Its Perception by Ticinese Artists of Empire Style in Moscow - Klimenko, Julia G. (Actual Problems of Theory and History of Art, 2018)
The article is focused on the problem of perception of illustrated architectural editions by J.-Ch. Krafft in Russia, especially Recueil d’Architecture Civile with 120 plates representing the best of neoclassical French architecture. Numerous publications of this Almanac and handwritten copies of its engravings prove interest to the source of the most successful projects and show appreciation of a significant artifact of specific culture, which came to be highly esteemed only after the loss of many monuments during the French revolution.While the value of this deluxe illustrated edition for Russia where active construction of mansions demanded proved architectural examples is obvious, for a long time researchers failed to uncover any facts showing its presence or use by clients or architects. Thus, finding out some traces of the use of the edition is a certain discovery. These traces were found in the archive of Luigi Pelli, a Swiss architect who worked in Moscow and other Russian towns. He graduated from Brera Academy of Fine Arts in Milan; so, he came to Russia with some real experience of construction. The architect’s family keeps his multiple projects and sketches showing many buildings of Moscow and Moscow region. Handmade copies of Krafft’s Almanac make up a significant part of these graphic documents.We need to determine a role of each of these architects to learn the overall significance of their community and to understand the context of their school. As long as we are able to find out the sources of specific borrowings we can hope to correct a range of wrong views and revise attribution of edifices in Moscow and rural areas in the construction of which Italian and Ticinese artists participated.
Keywords: architectural treatises; attribution; Age of Enlightenment; J.-Ch. Krafft; Empire style; Luigi Pelli; Domenico Gilardi; Alessandro Gilardi